Serum eosinophilic cationic protein is correlated with food impaction and endoscopic severity in eosinophilic esophagitis - Cem Cengiz (Turkish Journal of Gastroenterology, 2019)
Background/Aims: The aim of the present study was to analyze the diagnostic accuracy of serum eosinophilic cationic protein (ECP) for eosinophilic esophagitis (EoE) and the correlation of ECP with clinical, histopathological, laboratory, and endoscopic features of EoE. Materials and Methods: Fifteen patients with EoE and 14 healthy controls were included in the study. Demographic parameters were recorded. EoE Endoscopic Reference Score (EREFS) was calculated according to endoscopic features, and esophageal biopsies were obtained by a single experienced endoscopist in a patient group. Serum ECP levels (μg/mL), absolute eosinophil count (U/mm3), and maximum peak of eosinophils/high-power field in esophageal biopsies were analyzed. Results: The median age of all participants was 33.0 (min-max: 18-46) years. There were 27 (93.1%) male patients. Serum ECP level was significantly higher in patients with EoE than in healthy volunteers (20.4 vs. 8.8, p<0.0001). According to the receiver operating characteristic (ROC) curve analysis, ECP had 80% sensitivity and 92.8% specificity to diagnose EoE with a cut-off value of 13.9 µg/mL (area under the ROC curve 0.895; p<0.0001; 95% CI: 0.725-0.978). EREFS (p<0.0001) and the presence of food impaction (p=0.04) were significantly correlated with ECP. Conclusion: Serum ECP is an accurate non-invasive biomarker for EoE with high specificity and sensitivity. In addition, ECP is strongly correlated with EREFS and the symptom of food impaction. Cite this article as: Cengiz C. Serum eosinophilic cationic protein is correlated with food impaction and endoscopic severity in eosinophilic esophagitis. Turk J Gastroenterol 2019; 30(4): 345-49.